(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2019)
Background: The TIMI (Thrombolysis in Myocardial Infarction) risk score is a seven item risk stratification tool derived from trials of patients with Unstable Angina (UA) that has been validated in Emergency Department (ED) patients with potential Acute Coronary Syndromes (ACS). To evaluate frequency, outcome and correlation of the gender variation of in-hospital outcome in patients of unstable angina by TIMI risk score. Materials and methods: This was an observational study of Cardiac Care Unit (CCU) patients with unstable angina. Data included demographics, medical and cardiac history, and components of the TIMI risk score. Investigators followed the hospital course daily. The outcomes were death, Acute Myocardial Infarction (AMI) heart failure and arrhythmia during hospital stay as stratified by TIMI risk score and compared between genders using 2 tests. Data were analyzed by SPSS version-19. Results: In this study 62% patients were male and 38% patients were female. 55.20% female had low TIMI score whereas 16.10% male and 18.40% female had very high TIMI scores. The mortality rate was 0% in low TIMI score but the rate was increased in high TIMI score e.g. 3.30% in male patients and 2.60% in female patients with unstable angina. The rate of occuring MI, Cardiogenic shock, Heart failure is increased respectively from low to high TIMI score. In case of Arrhythmia, 17.70% male and 15.70% female had low TIMI score whereas 25.80% male and 26.30% female had high TIMI score. Conclusion: The TIMI risk score successfully stratifies risk in both males and females with UA at the time of CCU presentation; however, males have worse outcome at low TIMI scores than female. JCMCTA 2018 ; 29 (2) : 35-40